2022
DOI: 10.4049/jimmunol.2100593
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-Mediated Neutrophil Extracellular Trap Formation Exacerbates Intestinal Ischemia/Reperfusion-Induced Acute Lung Injury

Abstract: Influx of activated neutrophils into the lungs is the histopathologic hallmark of acute lung injury (ALI) after intestinal ischemia/reperfusion (I/R). Neutrophils can release DNA and granular proteins to form cytotoxic neutrophil extracellular traps (NETs), which promotes bystander tissue injury. However, whether NETs are responsible for the remote ALI after intestinal I/R and the mechanisms underlying the dissemination of harmful gut-derived mediators to the lungs are unknown. In the C57BL/6J mouse intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…In addition, IL-1β levels, blood BUN, creatinine and ALT were remarkably elevated in NEC + Cl-amidine compared with NEC pups, suggesting that inhibition of NETs appears to further exacerbate systemic inflammation and organ damage in mouse NEC and is likely due to increased bacteremia [ 101 ]. Surprisingly, in a study by Vincent et al yielded seemingly contradictory findings by establishing a NEC mouse model different from DK-NEC model established by Chaaban et al They found that serum circulation free DNA (cfDNA) was positively correlated with clinical manifestations of NEC, and markers of neutrophil activation and NETs were significantly increased in animals suffering from NEC and in human samples compared to controls [ 102 ]. Prevention of NET formation in mice by suppressing PAD significantly reduced NEC-induced mortality, tissue lesions and deterioration in mice.…”
Section: Nets and Intestinal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-1β levels, blood BUN, creatinine and ALT were remarkably elevated in NEC + Cl-amidine compared with NEC pups, suggesting that inhibition of NETs appears to further exacerbate systemic inflammation and organ damage in mouse NEC and is likely due to increased bacteremia [ 101 ]. Surprisingly, in a study by Vincent et al yielded seemingly contradictory findings by establishing a NEC mouse model different from DK-NEC model established by Chaaban et al They found that serum circulation free DNA (cfDNA) was positively correlated with clinical manifestations of NEC, and markers of neutrophil activation and NETs were significantly increased in animals suffering from NEC and in human samples compared to controls [ 102 ]. Prevention of NET formation in mice by suppressing PAD significantly reduced NEC-induced mortality, tissue lesions and deterioration in mice.…”
Section: Nets and Intestinal Inflammationmentioning
confidence: 99%
“…Prevention of NET formation in mice by suppressing PAD significantly reduced NEC-induced mortality, tissue lesions and deterioration in mice. What's more interesting is that immunohistochemical results of mouse NEC model were positively correlated with the results of human NEC specimens, the NETs marker observed in mice could potentially be used to study the pathogenesis of human NEC [ 102 ]. Similar conclusions were reached in the study by Klinke et al .…”
Section: Nets and Intestinal Inflammationmentioning
confidence: 99%
“…Following ischemia–reperfusion of the kidney, neutrophils infiltrate the lung, increasing cytokine secretion, and NET formation, which was ameliorated upon PAD4 inhibition, thereby reducing ischemia–reperfusion-consecutive lung injury [ 159 ]. Doi and colleagues [ 160 ] revealed that ALI following AKI depends on HMGB1, which is further underlined by a recently published study demonstrating that acute lung injury following intestinal ischemia–reperfusion depends on HMGB1-induced NET formation, associated with tissue inflammation, and pathological injury in the lung [ 112 , 161 ]. In line with this, histones have detrimental effects on alveolar cells in vitro and in vivo during transfusion-related lung injury [ 75 , 162 ].…”
Section: Organ Dysfunction and Remote Organ Injurymentioning
confidence: 99%
“…Over the past 20 years, the scientific community has come to a fundamental understanding of how platelets possibly stimulate neutrophils to cast NETs. There are mainly two mechanisms which are described, that can lead to platelet-induced NETosis: first, as the result of direct cell-cell contact and receptor-ligand interaction between platelets and neutrophils, respectively ( 14 ), or second, initiated through platelet-derived soluble mediators ( 15 , 16 ) ( Figure 1 ). However, a role for the synergistic action of both mechanisms must not be neglected ( 17 ).…”
Section: Platelets Stimulate Neutrophils For Netosismentioning
confidence: 99%